Red Cotton Stamen Extracts Mitigate Ferrous Sulfate-Induced Oxidative Stress and Enhance Quality in Bull Frozen Semen - Jiraporn Laoung-on; Jakree Jitjumnong; Paiwan Sudwan; Nopparuj Outaitaveep; Sakaewan Ounjaijean; Kongsak Boonyapranai (Veterinary Sciences)
Infertility is a significant global health concern, and incorporating antioxidants into sperm preparation media is one strategy to enhance sperm quality and decrease infertility rates. This study aimed to investigate the phytochemical compounds of red cotton stamen extracts and their effects as antioxidants in improving the quality of bull frozen semen. Among the extracts, RCU contained the highest levels of total phenolics, total tannins, and total monomeric anthocyanins along with the strongest ABTS free radical scavenging activity and protein denaturation inhibition. Exposing sperm to FeSO4-induced oxidative stress resulted in significantly reduced motility, viability, and normal morphology. However, treatment with RCD, RCU, and RCM improved these parameters. Additionally, the FeSO4-induced group showed elevated levels of reactive oxygen species (ROS) and advanced glycation end products (AGEs) compared to the normal control, whereas all red cotton stamen extracts effectively reduced these levels. In conclusion, red cotton stamen extracts, rich in phenolic bioactive compounds, demonstrated strong free radical scavenging capacity and improved sperm motility, viability, and morphology by neutralizing free radicals and enhancing antioxidant defenses. These findings suggest that the red cotton stamen extracts, particularly RCD and RCU, offer benefits for sperm preservation.